A novel hybrid tobacco product that delivers a tobacco flavour note with vapour aerosol (Part 2): In vitro biological assessment and comparison with different tobacco-heating products. (August 2017) - Breheny, Damien; Adamson, Jason; Azzopardi, David; Baxter, Andrew; Bishop, Emma; Carr, Tony; Crooks, Ian; Hewitt, Katherine; Jaunky, Tomasz; Larard, Sophie; Lowe, Frazer; Oke, Oluwatobiloba; et al.
Abstract: This study assessed the toxicological and biological responses of aerosols from a novel hybrid tobacco product. Toxicological responses from the hybrid tobacco product were compared to those from a commercially available Tobacco Heating Product (c-THP), a prototype THP (p-THP) and a 3R4F reference cigarette, using in vitro test methods which were outlined as part of a framework to substantiate the risk reduction potential of novel tobacco and nicotine products. Exposure matrices used included total particulate matter (TPM), whole aerosol (WA), and aqueous aerosol extracts (AqE) obtained after machine-puffing the test products under the Health Canada Intense smoking regime. Levels of carbonyls and nicotine in these matrices were measured to understand the aerosol dosimetry of the products. The hybrid tobacco product tested negative across the in vitro assays including mutagenicity, genotoxicity, cytotoxicity, tumour promotion, oxidative stress and endothelial dysfunction. All the THPs tested demonstrated significantly reduced responses in these in vitro assays when compared to 3R4F. The findings suggest these products have the potential for reduced health risks. Further pre-clinical and clinical assessments are required to substantiate the risk reduction of these novel products at individual and population levels. Highlights: Aerosol produced from a novel hybrid tobacco product was assessed for biological activity using a suite of in vitro assays. The in vitro responses were compared with those induced by tobacco-heating products and a reference cigarette. In vitro dosimetry methods were applied to assess the levels of key toxicants in the aerosol exposure matrices. The hybrid tobacco product demonstrated significant reductions in biological activity compared to the reference cigarette. The hybrid tobacco product also showed lower activity than tobacco-heating products in many of these tests.